2008
DOI: 10.1111/j.1440-1746.2008.05555.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transnasal ultrathin esophagogastroduodenoscopy (UT‐EGD) in the evaluation of esophageal peristaltic function

Abstract: The use of an ultrathin transnasal endoscope makes possible simultaneous manometry and endoscopic observation of the esophagus. This combination should prove useful in the evaluation of esophageal peristaltic function, such as in the diagnosing of GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“… 28 Furthermore, Kawai et al. 29 reported a new method to evaluate esophageal peristaltic function with an intraesophageal manometry probe passed through the accessory channel of an ultrathin scope inserted transnasally. This combination of simultaneous endoscopy and manometry shows promise for screening of peristaltic function.…”
Section: Recently Reported Endoscopic Techniques With Transnasal Scopmentioning
confidence: 99%
“… 28 Furthermore, Kawai et al. 29 reported a new method to evaluate esophageal peristaltic function with an intraesophageal manometry probe passed through the accessory channel of an ultrathin scope inserted transnasally. This combination of simultaneous endoscopy and manometry shows promise for screening of peristaltic function.…”
Section: Recently Reported Endoscopic Techniques With Transnasal Scopmentioning
confidence: 99%
“…After the scope had been passed into the esophagus transnasally, a 5Fr manometry catheter was inserted from the forceps channel and the intraesophageal pressure was measured. This procedure enabled simultaneous endoscopic observation of esophageal peristaltic activity and measurement of the maximal peristaltic pressure in lower esophagus after the wet swallow …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the combination of vision and manometry has been attempted previously. Kawai et al 6 reported that transnasal ultrathin EGD and simultaneous esophageal manometry are useful in the evaluation of esophageal peristaltic function. However, the manometry catheter used in that study was inserted through the scope and only evaluated the area in front of the scope.…”
Section: Discussionmentioning
confidence: 99%
“…The impedance catheter was inserted through the scope and had the same diagnostic limitations as those in the study by Kawai et al 6 Those 2 studies used conventional EGD to view the esophagus and inserted the new catheters through the scope, with neither functioning as a technique for whole esophageal monometry or impedance. [6][7][8] The new vision-assisted catheter has several limitations. The optic module has no function for lens cleaning or air inflation, which is important for clear vision.…”
Section: Discussionmentioning
confidence: 99%